A randomized, double blind, placebo controlled, multicenter clinical trial to assess the efficacy and safety of Emblica officinalis extract in patients with dyslipidemia - Haridas Upadya; S. Prabhu; Aravinda Prasad; Deepa Subramanian; Swati Gupta; Ajay Goel (BMC, 2019)
Abstract Background Dyslipidemia is one of the most frequently implicated risk factors for development of atherosclerosis. This study evaluated the efficacy of amla (Emblica officinalis) extract (composed of polyphenols, triterpenoids, oils etc. as found in the fresh wild amla fruit) in patients with dyslipidemia. Methods A total of 98 dyslipidemic patients were enrolled and divided into amla and placebo groups. Amla extract (500 mg) or a matching placebo capsule was administered twice daily for 12 weeks to the respective group of patients. The patients were followed up for 12 weeks and efficacy of study medication was assessed by analyzing lipid profile. Other parameters evaluated were apolipoprotein B (Apo B), apolipoprotein A1 (Apo A1), Coenzyme Q10 (CoQ10), high-sensitive C-reactive protein (hsCRP), fasting blood sugar (FBS), homocysteine and thyroid stimulating hormone (TSH). Results In 12 weeks, the major lipids such as total cholesterol (TC) (p = 0.0003), triglyceride (TG) (p = 0.0003), low density lipoprotein cholesterol (LDL-C) (p = 0.0064) and very low density lipoprotein cholesterol (VLDL-C) (p = 0.0001) were significantly lower in amla group as compared to placebo group. Additionally, a 39% reduction in atherogenic index of the plasma (AIP) (p = 0.0177) was also noted in amla group. The ratio of Apo B to Apo A1 was reduced more (p = 0.0866) in the amla group as compared to the placebo. There was no significant change in CoQ10 level of amla (p = 0.2942) or placebo groups (p = 0.6744). Although there was a general trend of FBS reduction, the numbers of participants who may be classified as pre-diabetes and diabetes groups (FBS > 100 mg/dl) in the amla group were only 8. These results show that the amla extract used in the study is potentially a hypoglycaemic as well. However, this needs reconfirmation in a larger study. Conclusions The Amla extract has shown significant potential in reducing TC and TG levels as well as lipid ratios, AIP and apoB/apo A-I in dyslipidemic persons and thus has scope to treat general as well as diabetic dyslipidemia. A single agent to reduce cholesterol as well as TG is rare. Cholesterol reduction is achieved without concomitant reduction of Co Q10, in contrast to what is observed with statins. Trial registration Registered with Clinical Trials Registry- India at www.ctri.nic.in (Registration number: CTRI/2015/04/005682) on 8 April 2015 (retrospectively registered).